A Short Note on the Fallacy of Identification of Technological Progress in Models of Economic Growth. (13th April 2015) - Acikgoz, Senay; Mert, Merter
This study emphasizes the necessity of the Harrod-neutral identification of technological progress for the models of economic growth, which use Cobb–Douglas production function and which are based on stability. Some of the important studies, which reviewed a balanced growth path or a steady state of the Solow model, assumed the nature of technological progress as Hicks-neutral rather than Harrod-neutral. In this work, we have reminded that Harrod-neutral is a better assumption for the nature of technological progress in such studies.